Ferrocene Derivatives Carrying Urea, Thiourea, and Sulfonamide Moieties: Synthesis and Evaluation of Antibacterial and Antifungal Activities - Serkan Yavuz; Hilal Yıldırım (Journal of Chemistry)
In the present study, some novel ferrocene derivatives carrying urea, thiourea, and sulfonamide groups were synthesized, and all compounds were characterized by spectral and elemental analyses. These compounds were screened for their antibacterial activities and also their minimum inhibitory concentration (MIC) against Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis) and Gram-negative bacteria (Klebsiella pneumonia and Escherichia coli) and antifungal activities against Saccharomyces cerevisiae and Candida albicans. Amongst the tested compounds, 4b, 4c, 5b, and 6b displayed excellent antimicrobial activity.